Potential value of neuroimmunotherapy for COVID-19: efficacies and mechanisms of vagus nerve stimulation, electroacupuncture, and cholinergic drugs - Yu, Xianqiang; Kong, Qingming (Frontiers in Immunology, 2023)
COVID-19 is an inflammatory disease with multiple organs involved, mainly respiratory symptoms. Although the majority of patients with COVID-19 present with a mild to moderate self-limited course of illness, about 5-10% of patients with inflammatory disorders in severe COVID-19 have life-threatening progression. However, there is currently no effective antiviral treatment strategy for SARS-COV-2.With the exception of a few drugs that have shown outstanding anti-COVID-19 effects, the efficacy of most drugs remains controversial. An increasing number of animal and clinical studies have shown that neuromodulation has a significant effect on reducing inflammatory markers of COVID-19, thus exerting an effective neuroimmunotherapeutic value. Currently, the main neuroimmunomodulatory measures effective against COVID-19 include vagus nerve stimulation, electroacupuncture, and cholinergic drugs. In this review, we will summarize the research progress of potential value of this neuroimmunotherapy measures for COVID-19 and elaborate its efficacies and mechanisms, in order to provide reliable evidence for clinical intervention.